2021
DOI: 10.31812/123456789/4628
|View full text |Cite
|
Sign up to set email alerts
|

Improving the learning environment for future mathematics teachers with the use application of the dynamic mathematics system GeoGebra AR

Abstract: Immersive technologies and, in particular, augmented reality (AR) are rapidly changing the sphere of education, especially in the field of science, technology, engineering, arts and mathematics. High- quality professional training of a future mathematics teacher who is able to meet the challenges that permeate all sides, the realities of the globalizing information society, presupposes reliance on a highly effective learning environment. The purpose of the research is to transform the traditional educational e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 89 publications
0
2
0
1
Order By: Relevance
“…Moreover, Albano & Dello Iacono (2019) revealed that learning by using Geogebra is positively making the students' learning atmosphere getting better and more convenient. Osypova & Tatochenko (2021) emphasized that, in the future, all teachers must utilize the application Geogebra to support teaching learning in the classroom because this software effectively helps everyone to understand mathematics, mainly to understand Geometry much easier. In addition, Wassie & Zergaw (2019) explained that by using Geogebra, students can travel via virtual geometry joyfully, and their ability in spatial getting better.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Albano & Dello Iacono (2019) revealed that learning by using Geogebra is positively making the students' learning atmosphere getting better and more convenient. Osypova & Tatochenko (2021) emphasized that, in the future, all teachers must utilize the application Geogebra to support teaching learning in the classroom because this software effectively helps everyone to understand mathematics, mainly to understand Geometry much easier. In addition, Wassie & Zergaw (2019) explained that by using Geogebra, students can travel via virtual geometry joyfully, and their ability in spatial getting better.…”
Section: Discussionmentioning
confidence: 99%
“…The application of Geogebra in learning also prepares students to face more complex mathematical challenges in the future (Osypova & Tatochenko, 2021). They become familiar with the use of technology in a mathematical context and develop computing and problemsolving skills that are essential for success in an increasingly connected and technologydriven world.…”
Section: Figure 1 Effect Size Of the Articlementioning
confidence: 99%
“…Педагоги озвучували проблему добору інструментарію для використання вільно поширених і створення власних AR-об'єктів (Н. В. Осипова, В. І. Таточенко) [51]. Значний внесок у розкриття питання зроблено вченими Л.Ф.…”
Section: проблематика використання технології доповненої реальності в...unclassified